2014
DOI: 10.7896/j.1320
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis and labour force transition to inactivity: a comparative study in German rural and urban areas

Abstract: Economic crisis and labour force transition to inactivity: a comparative study in German rural and urban areasThis study analyses the determinants of labour force transition to inactivity in the German labour market. Using German Labour Force Survey data the infl uence on the transition fl ow to inactivity of factors such as age, education, marital status, sex and registration with the public employment service are examined. We present estimates of degree of urbanisation-specifi c multinominal logit models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Further, it is highly likely that during the crisis period factors that influence transition flow differs in rural and urban regions in Germany. 21 Based on our simulation findings, it was shown that even though the simulation was able to correctly replicate past trends before the crisis, it was impossible to reproduce post-crisis trends given that the dynamics were strongly affected by external factors not considered in the model. Such an impact should serve as a reminder of the limitation of these types of models.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Further, it is highly likely that during the crisis period factors that influence transition flow differs in rural and urban regions in Germany. 21 Based on our simulation findings, it was shown that even though the simulation was able to correctly replicate past trends before the crisis, it was impossible to reproduce post-crisis trends given that the dynamics were strongly affected by external factors not considered in the model. Such an impact should serve as a reminder of the limitation of these types of models.…”
Section: Resultsmentioning
confidence: 91%
“…Further, it is highly likely that during the crisis period factors that influence transition flow differs in rural and urban regions in Germany. 21…”
Section: Discussionmentioning
confidence: 99%
“…Gailhard and Kataria (2014) introduce several factors, which might explain the flow between inactive and employed. As German data (similarly to other publications) shows that the probability to be reemployed is similar both in case of unemployed and inactive, and as such the differences cannot be simply explained by active job search or no search at all.…”
Section: Debate Of Employment Unemployment Inactivity Definition Amentioning
confidence: 99%